Multidecadal wind‐driven shifts in northwest Pacific temperature, salinity, O2, and PO4. Issue 11 (3rd November 2016) - Kwon, Eun Young; Kim, Young Ho; Park, Young‐Gyu; Park, Young‐Hyang; Dunne, John; Chang, Kyung‐Il
Abstract: The North Pacific gyre boundaries are characterized by stark contrasts in physical and biogeochemical properties. Meridional movement of gyre boundaries, influenced by climate change, can therefore exert a large influence not only on marine ecosystems but also on climate. We examine the evidence for wind‐driven southward shifts in subsurface temperature, salinity, PO4, and O2 within the northwest Pacific from the 1950s to the 2000s. Gyre boundary shifts can explain 30–60% of temperature and salinity trends zonally averaged in the northwest Pacific and observed PO4 and O2 trends along the 137°E and 144°E meridians. The close tie between the wind‐driven shifts in gyre boundaries and the tracer distributions is further supported by results from an eddy‐resolving (0.1° × 0.1°) Geophysical Fluid Dynamics Laboratory climate model, suggesting that the physical and biogeochemical properties averaged within the northwest Pacific gyre boundaries closely follow the latitude changes of the zero Sverdrup stream function with lags of 0 to 3 years. The gyre shift effect on tracer distribution is poorly represented in a coarse resolution (1° × 1°) model due partly to poor representations of fronts and eddies. This study suggests that future changes in northwest Pacific PO4 and O2 content may depend not only on ocean temperature and stratification but also on the ocean gyre response to winds. Key Points: Historical data indicate southward shifts in O2 and PO4 from 1968 to 2007 The gyre shift can explain O2 and PO4 variability within gyre boundaries High‐resolution climate model supports the observation‐based finding